Current Clinical Profile of Enteric Fever in a Teaching Hospital - Kabir, Shahriar; Azhar, MA; Ekram, ARM Saifuddin; Islam, Quazi Tarikul; Ahmed, Iftekhar (TAJ: Journal of Teachers Association, 2009)
This study was designed to assess the current of clinical presentations, complications and prognosis of enteric fever cases in Bangladeshi population and also to assess the antimicrobial sensitivity of the causative organisms. A total of 65 patients, with either fever of any duration with positive blood culture for Salmonella, of fever of more than a week with strong clinical evidence of enteric fever along with single Widal titre TO >160 of AO >160 or BO> 160, were selected from indoor medical wards of Rajshahi Medical College Hospital from August 2000 to May 2001. Blood culture with sensitivity pattern, Widal tests and relevant investigations were done in all patients. Majority (87.70%) of the patients presented on the second or third week of their illness. Other clinical profiles of the patients were comparable to different studies done in our country and in abroad. Common complications were pneumonia, meningitis and typhoid psychosis. Isolated salmonellae from blood culture were 100% sensitive to Ciprofloxacin and Pefloxacin. Two out of sixty five patients (3.07%) expired due to complications. doi: 10.3329/taj.v15i2.3914 TAJ December 2002; Vol.15(2): 81-83